2023
DOI: 10.1186/s12875-023-01973-2
|View full text |Cite
|
Sign up to set email alerts
|

Workload and workflow implications associated with the use of electronic clinical decision support tools used by health professionals in general practice: a scoping review

Abstract: Background Electronic clinical decision support tools (eCDS) are increasingly available to assist General Practitioners (GP) with the diagnosis and management of a range of health conditions. It is unclear whether the use of eCDS tools has an impact on GP workload. This scoping review aimed to identify the available evidence on the use of eCDS tools by health professionals in general practice in relation to their impact on workload and workflow. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 113 publications
0
4
0
Order By: Relevance
“…Most studies did not precisely consider one medical specialty, disease, or condition. However, some reviews focused on diseases of the respiratory system (e.g., tuberculosis, asthma, and chronic pulmonary obstructive disease) 19 , 22 , 31 , 32 , 46 , 93 , 101 , 123 , pregnancy, childbirth, or puerperium (e.g., maternal health, postpartum hemorrhage, and reproductive health) 19 , 22 , 23 , 26 , 31 , 35 , 46 , 56 , 61 , 77 , 94 , certain infectious or parasitic diseases (e.g., malaria, human immunodeficiency virus infection, and influenza) 19 , 22 , 23 , 28 , 31 , 46 , 50 , 61 , endocrine, nutritional, or metabolic diseases (e.g., diabetes mellitus) 57 , 64 , 76 , 93 , 123 , mental and behavioral disorders (e.g., post-traumatic disorder syndrome, stress, depression, and burnout) 23 , 41 , 44 , 64 , 70 , 76 , 94 , 125 , neoplasms 50 , 67 , 85 , 123 , diseases of the circulatory system (e.g., hypertension) 19 , 25 , 48 , 50 , 57 , 67 , 93 , 123 , diseases of the blood or blood-forming organs (e.g., anemia) 22 , and diseases or disorders of orofacial complex (e.g., oral lesions) 28 , 42 . Identified reviews mostly included quantita...…”
Section: Resultsmentioning
confidence: 99%
“…Most studies did not precisely consider one medical specialty, disease, or condition. However, some reviews focused on diseases of the respiratory system (e.g., tuberculosis, asthma, and chronic pulmonary obstructive disease) 19 , 22 , 31 , 32 , 46 , 93 , 101 , 123 , pregnancy, childbirth, or puerperium (e.g., maternal health, postpartum hemorrhage, and reproductive health) 19 , 22 , 23 , 26 , 31 , 35 , 46 , 56 , 61 , 77 , 94 , certain infectious or parasitic diseases (e.g., malaria, human immunodeficiency virus infection, and influenza) 19 , 22 , 23 , 28 , 31 , 46 , 50 , 61 , endocrine, nutritional, or metabolic diseases (e.g., diabetes mellitus) 57 , 64 , 76 , 93 , 123 , mental and behavioral disorders (e.g., post-traumatic disorder syndrome, stress, depression, and burnout) 23 , 41 , 44 , 64 , 70 , 76 , 94 , 125 , neoplasms 50 , 67 , 85 , 123 , diseases of the circulatory system (e.g., hypertension) 19 , 25 , 48 , 50 , 57 , 67 , 93 , 123 , diseases of the blood or blood-forming organs (e.g., anemia) 22 , and diseases or disorders of orofacial complex (e.g., oral lesions) 28 , 42 . Identified reviews mostly included quantita...…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, uncertainty indicators or contingency messages where the model is unable to answer with accuracy could improve confidence in the information provided and, therefore, safety [ 19 , 20 ]. Specific study is required to ensure that new tools reduce rather than increase workload for GPs [ 23 - 25 ]. As this technology continues to advance, individualistic care must not be sacrificed: general practice consulting involves long-term development of a therapeutic relationship between patients and physicians, and chatbots should not be allowed to change this dynamic into an impersonal, transactional arrangement [ 21 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The data suggested that the idea of using a symptom‐based risk calculator was good if it would help earlier identification or referral, although research is yet to identify if clinical decision‐making tools are disruptive to consultation times, increasing them to an inappropriate degree 27 . Furthermore, the calculator does not include premalignant oral conditions such as leukoplakia, erythroplakia and oral lichen planus.…”
Section: Discussionmentioning
confidence: 99%
“…The data suggested that the idea of using a symptom-based risk calculator was good if it would help earlier identification or referral, although research is yet to identify if clinical decision-making tools are disruptive to consultation times, increasing them to an inappropriate degree. 27 Furthermore, the calculator does not include premalignant oral conditions such as leukoplakia, erythroplakia and oral lichen planus. Notwithstanding, for cancer symptoms such as an ulcer or a croaky voice, the calculator would result in the recommendation of an urgent referral if the symptoms were persistent and unexplained, even with an absence of a history of smoking or excess alcohol consumption.…”
Section: Hnc Presentation and Seeking Helpmentioning
confidence: 99%